Loss and Grief in the Context of the COVID-19 Pandemic in Brazil: The Role of Spirituality and Religiosity - Mary Rute Gomes Esperandio; Luciana Soares Rosas; Fabiana Torres Xavier; Arndt Büssing (Religions)
The COVID-19 pandemic has significantly altered the experience of loss and mourning, potentially increasing distress among bereaved individuals. This study aimed to assess this experience and examine the role of spirituality and religiosity in this context. Using a mixed-methods, cross-sectional design, this research employed a sociodemographic questionnaire, the Inventory of Complicated Grief (ICG), the WHO-5 Well-Being Index, the Burdened by Grief and Loss (BGL) scale, and an open-ended question regarding what participants found helpful in their grieving process. Of the 323 responses eligible for quantitative analysis, 225 participants responded to the open-ended question. Notably, 36.84% of the sample scored above 25 on the ICG, indicating significant grief-related distress. Quantitative findings revealed that individuals with spiritual engagement (religious or not) reported lower levels of grief and higher general well-being scores. Qualitative analysis of the open responses highlighted spirituality as the most prominent source of support in coping with grief during the pandemic. Given Brazil’s high mortality rate, a substantial number of people may be experiencing complications in their grieving processes. Healthcare professionals and spiritual/religious care providers should be equipped to offer appropriate support and foster interdisciplinary dialog to assist those bereaved effectively.